1990
DOI: 10.1002/cite.330621204
|View full text |Cite
|
Sign up to set email alerts
|

Exergetische Analyse und Bewertung verfahrenstechnischer Prozesse mit einem Flow‐Sheeting‐Programm

Abstract: Exergy analysis and assessment of process plants with flow-sheeting systems. Mass and enthalpy balances are necessary for the calculation and assessment of process plants. The economic and ecological results cannot be optimal because the different value of energy according to the Second Law of Thermodynamics and the influence of the environment are not included. This is accomplished by exergetic analysis and assessment. The aim is to obtain an exergy analysis and assessment of any procesSplant through combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…The molar exergy content of a material flow is composed of three terms [16], namely the chemical exergy E chem , the physical exergy E phys , and the mixing exergy E mix : chem phys mix…”
Section: Methodsmentioning
confidence: 99%
“…The molar exergy content of a material flow is composed of three terms [16], namely the chemical exergy E chem , the physical exergy E phys , and the mixing exergy E mix : chem phys mix…”
Section: Methodsmentioning
confidence: 99%
“…The problems associated with the last objection can be effectively addressed. Specific proposals and methodologies for defining a reference environment are available , , . For technical analyses, reference environment definitions based on abundant reference substances are used , .…”
Section: Application Of Exergy Analysis In Process Design Analysis mentioning
confidence: 99%
“…Another major advantage of exergy analysis is its easy integration into simulation programs , . However, different studies have shown that exergy analysis provides rather small benefits in combination with computer‐based mathematical optimization procedures , .…”
Section: Application Of Exergy Analysis In Process Design Analysis mentioning
confidence: 99%
“…Hence, there is very little information available about possible chemical processes as a basis for quantitative evaluation. The exergy of a material flow can be divided into three parts: chemical exergy, physical exergy, and exergy upon mixing [20][21][22]: However, material and energy balances are not sufficient for an initial evaluation because, e.g., the quality of various energy forms is not considered.…”
Section: Exergy Balances For Evaluation Of Synthesis Pathwaysmentioning
confidence: 99%
“…In this paper, T 0 = 298.15 K and p 0 = 101 325 Pa as temperature and pressure of the environment are assumed. The exergy of a material flow can be divided into three parts: chemical exergy, physical exergy, and exergy upon mixing [20][21][22]:…”
Section: Exergy Balances For Evaluation Of Synthesis Pathwaysmentioning
confidence: 99%